Technical tours as special interest tourism in the urban context: a case study of Kuala Lumpur - Zakariya, Khalilah; Che Haron, Roziha; Yusof, Zeenat Begam; Ibrahim, Illyani (e-International Publishing House, Ltd., UK., 2020)
tudies on Special Interest Tourism (SIT) have gained an increasing attention within the last decade. This article examined the potentials of attractions in Kuala Lumpur that can attract built environment professionals as a niche group of tourists. Based on analysing secondary data sourced from technical tours, tour packages and attractions promoted by different agencies, this study mapped, tabulated and examined existing buildings and sites with their unique characteristics. 58 buildings and sites showed potentials as tourism attractions for built environment professionals through technical tours. A customised experience can be high-yield as they are tailor-made to special interest tourists